Implementasi Peran Komisi Pemilihan Umum Kota Bandar Lampung Terhadap Peraturan Komisi Pemilihan Umum Pasal 10 Ayat 1b Dalam Melaksanakan Pendidikan Politik Bagi Pemilih Pemula Pada Pemilihan Wali Kota Bandar Lampung Tahun 2024 Perspektif Fiqh Siyasah - Rosalinda; Linda Firdawaty; Hervin Yoki Pradikta (CV Rewang Rencang, 2025)
This study aims to analyze the implementation of the role of the Bandar Lampung City Election Commission (KPU) in conducting political education for first-time voters in accordance with the Regulation of the General Election Commission Article 10 Paragraph 1B during the 2024 Bandar Lampung Mayor Election. Using the perspective of Fiqh Siyasah, the study identifies various supporting factors, such as the support of educational institutions and the enthusiasm of young voters, as well as obstacles, including budget constraints and low political awareness. The results indicate that optimizing political education programs through adequate budget allocation, the use of digital technology, and strategic collaboration with various stakeholders are effective steps to enhance the political participation of the younger generation.